Impact of hypertensive disorders of pregnancy on short- and long-term outcomes of pregnancy-associated hemorrhagic stroke - Fang, Mei; Wang, Jiayan; Wang, Zexu; Chen, Yuqi; Xu, Wei; Tao, Chuanyuan; Ma, Lu; You, Chao; Hu, Xin; Xia, Fan (Frontiers in Neurology, 2023)
Background and Purpose Though hypertension disorders of pregnancy (HDP) are recognized as independent pregnancy-associated stroke risk factors, few studies have considered their impact on stroke prognosis. Therefore, we intended to evaluate the impact of HDP on short- and long-term outcomes of pregnancy-associated hemorrhagic stroke (HS). Methods We conducted a retrospective analysis of patients admitted to our hospital from May 2009 to December 2021 with a diagnosis of pregnancy-associated HS. After dividing patients into two groups by the presence of a diagnosis of HDP or not, the short-(at the time of discharge) and long-term (after discharge follow-up) outcomes were compared by mRS (modified Rankin Scale) scores, as poor functional outcome defined as mRS>2. Adjusted odds ratios (OR) and 95% confidence intervals (CI) were reported. Results Twenty-two HDP and 72 non-HDP pregnancy-associated HS patients were enrolled and follow-up after 4.7 ± 3.6 years. There was no significant difference between the two groups regarding short-term outcomes, but patients with HDP were more likely to reach poor functional outcomes at long-term follow-up (aOR=4.47, 95% CI= 1.28 to 15.67, p=0.019). Conclusions In this retrospective study, women with hypertension disorders of pregnancy did not show worse short-term outcomes of pregnancy-associated hemorrhagic stroke compared to those without but had poorer long-term functional outcomes. This underlines the importance of prevention, recognition, and treatment of hypertension disorders in these women.